ReS2-based composite material as well as preparation method and application thereof
By growing the ReS2/CoS2 Schottky junction on the surface of the carrier, the problems of low electron transmission efficiency and poor oxygen evolution activity of ReS2-based materials are solved, and efficient dual-functional catalytic performance of hydrogen evolution and oxygen evolution is achieved, which has broad energy application prospects.
Patent Information
- Application Number
- CN202411369696.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-24
AI Technical Summary
The existing ReS2-based materials have problems of low electron transport efficiency and poor oxygen evolution activity in electrolytic water decomposition, making it difficult to become an ideal dual-function electrocatalyst.
By growing on the surface of the carrier surface, the nano -film array is formed, and the electronic structure is optimized with the Syntky interface, promoting electronic transmission, and preparing composite materials through the water thermal reaction method.
The efficient hydrogen analysis and oxygen analysis of the RES2 base material have been realized, and the stability of the electronic transfer rate and the stability of the material has been improved, and the application prospects of the energy industry have a broad energy industry.
Smart Images

Figure CN119352079A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrocatalysis technology, and in particular to a ReS2-based composite material and a preparation method and application thereof. Background Art
[0002] Hydrogen energy is considered to be an ideal alternative energy source due to its advantages of zero carbon emissions, high energy conversion efficiency and high energy density. Hydrogen production by water electrolysis has the advantages of high product purity and eco-friendliness, and is widely regarded as an efficient and environmentally friendly way to produce hydrogen. Electrocatalysts can reduce the overpotential of the reaction and improve the catalytic efficiency. At present, precious metal Pt-based and RuO2 / IrO2-based materials are recognized as the best catalysts for cathode hydrogen evolution reaction and anode oxygen evolution reaction, respectively. However, the high price, scarce reserves and single selectivity of precious metals have greatly limited their large-scale commercial application. In addition, the use of electrocatalysts with dual-functional activity for hydrogen and oxygen evolution can simplify the electrolysis device, reduce the preparation cost and avoid cross-contamination of different electrode materials. Therefore, it is urgent to study and develop cheap and efficient bifunctional non-precious metal water electrolysis catalysts.
[0003] Faced with this problem, transition metal (Fe, Co, Ni, Re, etc.) based sulfides have been widely studied and applied in water electrolysis reactions. Among them, ReS2 has weak interlayer coupling, abundant edge sites and fast electrolyte transport properties, and is a highly anticipated hydrogen evolution catalyst. However, its slow electron transfer efficiency and poor oxygen evolution activity make it difficult to become an ideal bifunctional electrocatalyst. Therefore, it is crucial and challenging to adopt appropriate strategies to endow ReS2-based materials with efficient bifunctional water electrolysis catalytic activity. Summary of the invention
[0004] Purpose of the invention: The first purpose of the present invention is to provide a ReS2-based composite material that achieves efficient dual-functional catalytic performance of hydrogen evolution and oxygen evolution; the second purpose of the present invention is to provide a method for preparing the ReS2-based composite material; the third purpose of the present invention is to provide the application of the ReS2-based composite material in the electrolysis of water to produce H2 and O2.
[0005] Technical solution: The ReS2-based composite material described in the present invention includes a carrier and a ReS2 / CoS2 Schottky junction grown on the surface of the carrier, and the Schottky junction is a nanosheet array.
[0006] The rich Schottky interface between ReS2 and CoS2 promotes spontaneous electron transfer, which can optimize the electronic structure at the interface, promote electron transport, and improve the catalytic activity of hydrogen and oxygen evolution of the material. The ReS2 / CoS2 Schottky junction is a nanosheet array with a large specific surface area, which is conducive to the transmission and diffusion of electrolytes.
[0007] Preferably, the molar ratio of cobalt in the cobalt salt to rhenium in the rhenium source in the ReS2 / CoS2 Schottky junction is 1:(1-3). As the rhenium content increases, the catalytic performance of the composite material shows a "volcano graph" trend, and the catalytic performance is optimal when the molar ratio of cobalt to rhenium is 1:2.
[0008] Preferably, the carrier is carbon cloth. Carbon cloth as a carrier can effectively improve the conductivity of the material, and at the same time can prevent the aggregation of the loaded species and improve the stability of the material.
[0009] The preparation method of the ReS2-based composite material described in the present invention comprises the following steps: adding metal cobalt salt, rhenium source and sulfur source into a solvent and mixing them, adding carbon cloth, and then performing a hydrothermal reaction, rinsing and drying after completion, so as to obtain the ReS2-based composite material.
[0010] Preferably, the temperature of the hydrothermal reaction is 180-220°C.
[0011] Preferably, the reaction time is 20 to 28 hours.
[0012] Preferably, the metal cobalt salt is at least one of cobalt chloride, cobalt nitrate and cobalt sulfate.
[0013] Preferably, the rhenium source is ammonium perrhenate.
[0014] Preferably, the sulfur source is thiourea. The sulfur source reacts with cobalt and rhenium to generate ReS2 and CoS2, and an excess of sulfur is generally used.
[0015] The ReS2-based composite material described in the present invention is used in the electrolysis of water to produce H2 and O2.
[0016] Invention Mechanism: The composite material obtained by the present invention retains the hydrogen evolution activity of ReS2 and introduces CoS2 with oxygen evolution activity, so that it has dual-functional catalytic activity of hydrogen and oxygen evolution. In addition, the present invention generates a ReS2 / CoS2 Schottky junction on the surface of the carrier through a one-step hydrothermal reaction in the form of a nanosheet array, which has a large specific surface area and is conducive to the transmission and diffusion of the electrolyte, thereby improving the dual-functional catalytic activity. More importantly, the ReS2 and CoS2 lattices match to form a tight heterogeneous interface; the difference in work function between the two induces the generation of a Schottky barrier at the interface, causing the electronic structure to rearrange, forming a directional built-in electric field, and increasing the electron transfer rate, thereby further enhancing the dual-functional catalytic performance of the composite material.
[0017] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) By introducing CoS2 on the basis of ReS2 to form a Schottky junction, efficient dual-functional catalytic performance of hydrogen evolution and oxygen evolution is achieved; (2) The active component loaded on the carbon cloth is a ReS2 / CoS2 Schottky junction, which has the characteristics of multiple active sites, high electrocatalytic activity and high stability. It is a very potential catalyst for water electrolysis and is expected to have broad application prospects in the energy industry in the future; (3) The method of the present invention is simple to operate, the reactants are widely available, and it is easy to scale up production. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a scanning electron microscope (SEM) image of the carbon cloth-supported ReS2 / CoS2 Schottky junction composite material prepared in Example 1;
[0019] Figure 2 This is a high-resolution SEM image of the carbon cloth-supported ReS2 / CoS2 Schottky junction composite material prepared in Example 1;
[0020] Figure 3 is a transmission electron microscope (TEM) spectrum of the carbon cloth-supported ReS2 / CoS2 Schottky junction composite material prepared in Example 1;
[0021] Figure 4 This is the high resolution TEM (HRTEM) spectrum of the carbon cloth-supported ReS2 / CoS2 Schottky junction composite material prepared in Example 1
[0022] Figure 5 is the X-ray diffraction (XRD) pattern of the carbon cloth-supported ReS2 / CoS2 Schottky junction composite material prepared in Example 1;
[0023] Figure 6 It is the ultraviolet photoelectron spectroscopy (UPS) spectrum of the carbon cloth-supported ReS2 and carbon cloth-supported CoS2 prepared in Comparative Examples 1 and 2;
[0024] Figure 7 The distribution is the energy band diagram of (a) carbon cloth-supported ReS2 and carbon cloth-supported CoS2 prepared in Comparative Examples 1 and 2 and (b) carbon cloth-supported ReS2 / CoS2 Schottky junction composite material prepared by the method of Example 1;
[0025] Figure 8 It is a test spectrum of alkaline hydrogen evolution performance of the carbon cloth-supported ReS2 / CoS2 Schottky junction composite materials prepared in Example 1, Example 6, Example 7, Comparative Example 3 and Comparative Example 4, the carbon cloth-supported ReS2 prepared in Comparative Example 1, and the carbon cloth-supported CoS2 prepared in Comparative Example 2;
[0026] Fig. 9This is a test spectrum of the alkaline hydrogen evolution stability of the carbon cloth-supported ReS2 / CoS2 Schottky junction composite material prepared in Example 1;
[0027] Fig.10 It is a test graph of alkaline oxygen evolution performance of the carbon cloth-supported ReS2 / CoS2 Schottky junction composite materials prepared in Example 1, Example 6, Example 7, Comparative Example 3 and Comparative Example 4, the carbon cloth-supported ReS2 prepared in Comparative Example 1, and the carbon cloth-supported CoS2 prepared in Comparative Example 2;
[0028] Fig.11 This is a test graph of alkaline oxygen evolution stability of the carbon cloth-supported ReS2 / CoS2 Schottky junction composite material prepared in Example 1;
[0029] Fig.12 It is the alkaline complete water splitting performance test spectrum of the carbon cloth-supported ReS2 / CoS2 Schottky junction composite materials prepared in Example 1, Example 6, Example 7, Comparative Example 3 and Comparative Example 4, the carbon cloth-supported ReS2 prepared in Comparative Example 1, and the carbon cloth-supported CoS2 prepared in Comparative Example 2;
[0030] Fig.13 This is the alkaline complete water splitting stability test spectrum of the carbon cloth-loaded ReS2 / CoS2 Schottky junction composite material prepared in Example 1. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further described below in conjunction with embodiments.
[0032] Example 1
[0033] The ReS2-based composite material of the present invention comprises the following steps:
[0034] Weigh 0.33mmol Co(NO3)2·6H2O and 0.66mmol NH4ReO4, add to 30mL deionized water, stir to dissolve; then add 4mmol C2H4NS, stir for 30min, place in a 50mL reactor, and add a piece of carbon cloth with a size of 2*4, then hydrothermally react in an oven at 200℃ for 24h. After the reaction is completed, rinse the carbon cloth with water and ethanol in turn. After the sample is dried, a carbon cloth-loaded ReS2 / CoS2 Schottky junction composite material is obtained.
[0035] Example 2
[0036] The ReS2-based composite material of the present invention comprises the following steps:
[0037] Weigh 0.33mmol Co(NO3)2·6H2O and 0.66mmol NH4ReO4, add into 30mL deionized water, stir to dissolve; then add 4mmol C2H4NS, stir for 30min, place in a 50mL reactor, add a piece of carbon cloth of size 2*4, then hydrothermally react in an oven at 180℃ for 24h. After the reaction is completed, rinse the carbon cloth with water and ethanol in turn. After the sample is dried, a carbon cloth-loaded ReS2 / CoS2 Schottky junction composite material is obtained.
[0038] Example 3
[0039] The ReS2-based composite material of the present invention comprises the following steps:
[0040] Weigh 0.33mmol Co(NO3)2·6H2O and 0.66mmol NH4ReO4, add into 30mL deionized water, stir to dissolve; then add 4mmol C2H4NS, stir for 30min, place in a 50mL reactor, add a piece of carbon cloth of size 2*4, then hydrothermally react in an oven at 190℃ for 24h. After the reaction is completed, rinse the carbon cloth with water and ethanol in turn. After the sample is dried, a carbon cloth-loaded ReS2 / CoS2 Schottky junction composite material is obtained.
[0041] Example 4
[0042] The ReS2-based composite material of the present invention comprises the following steps:
[0043] Weigh 0.33mmol Co(NO3)2·6H2O and 0.66mmol NH4ReO4, add into 30mL deionized water, stir to dissolve; then add 4mmol C2H4NS, stir for 30min, place in a 50mL reactor, and add a piece of carbon cloth of size 2*4, then hydrothermally react in an oven at 210℃ for 24h. After the reaction is completed, rinse the carbon cloth with water and ethanol in turn. After the sample is dried, a carbon cloth-loaded ReS2 / CoS2 Schottky junction composite material is obtained.
[0044] Example 5
[0045] The ReS2-based composite material of the present invention comprises the following steps:
[0046] Weigh 0.33mmol Co(NO3)2·6H2O and 0.66mmol NH4ReO4, add into 30mL deionized water, stir to dissolve; then add 4mmol C2H4NS, stir for 30min, place in a 50mL reactor, add a piece of carbon cloth of size 2*4, then hydrothermally react in an oven at 220℃ for 24h. After the reaction is completed, rinse the carbon cloth with water and ethanol in turn. After the sample is dried, a carbon cloth-loaded ReS2 / CoS2 Schottky junction composite material is obtained.
[0047] Example 6
[0048] The ReS2-based composite material of the present invention comprises the following steps:
[0049] Weigh 0.33mmol Co(NO3)2·6H2O and 0.33mmol NH4ReO4, add into 30mL deionized water, stir to dissolve; then add 4mmol C2H4NS, stir for 30min, place in a 50mL reactor, add a piece of carbon cloth of size 2*4, then hydrothermally react in an oven at 200℃ for 24h. After the reaction is completed, rinse the carbon cloth with water and ethanol in turn. After the sample is dried, a carbon cloth-loaded ReS2 / CoS2 Schottky junction composite material is obtained.
[0050] Example 7
[0051] The ReS2-based composite material of the present invention comprises the following steps:
[0052] Weigh 0.33mmol Co(NO3)2·6H2O and 0.99mmol NH4ReO4, add to 30mL deionized water, stir to dissolve; then add 4mmol C2H4NS, stir for 30min, place in a 50mL reactor, and add a piece of carbon cloth with a size of 2*4, then hydrothermally react in an oven at 200℃ for 24h. After the reaction is completed, rinse the carbon cloth with water and ethanol in turn. After the sample is dried, a carbon cloth-loaded ReS2 / CoS2 Schottky junction composite material is obtained.
[0053] Example 8
[0054] The ReS2-based composite material of the present invention comprises the following steps:
[0055] Weigh 0.33mmol Co(NO3)2·6H2O and 0.66mmol NH4ReO4, add to 30mL deionized water, stir to dissolve; then add 3mmol C2H4NS, stir for 30min, place in a 50mL reactor, and add a piece of carbon cloth of size 2*4, then hydrothermally react in an oven at 200℃ for 24h. After the reaction is completed, rinse the carbon cloth with water and ethanol in turn. After the sample is dried, a carbon cloth-loaded ReS2 / CoS2 Schottky junction composite material is obtained.
[0056] Example 9
[0057] The ReS2-based composite material of the present invention comprises the following steps:
[0058] Weigh 0.33mmol CoCl2·6H2O and 0.66mmol NH4ReO4, add to 30mL deionized water, stir to dissolve; then add 4mmol C2H4NS, stir for 30min, place in a 50mL reactor, and add a piece of carbon cloth with a size of 2*4, then hydrothermally react in an oven at 200℃ for 24h. After the reaction is completed, rinse the carbon cloth with water and ethanol in turn. After the sample is dried, a carbon cloth-loaded ReS2 / CoS2 Schottky junction composite material is obtained.
[0059] Example 10
[0060] The ReS2-based composite material of the present invention comprises the following steps:
[0061] Weigh 0.33mmol CoSO4 7H2O and 0.66mmol NH4ReO4, add into 30mL deionized water, stir to dissolve; then add 4mmol C2H4NS, stir for 30min, place in a 50mL reactor, add a piece of carbon cloth of size 2*4, then hydrothermally react in an oven at 200℃ for 24h. After the reaction is completed, rinse the carbon cloth with water and ethanol in turn. After the sample is dried, a carbon cloth-loaded ReS2 / CoS2 Schottky junction composite material is obtained.
[0062] Embodiment 11
[0063] The ReS2-based composite material of the present invention comprises the following steps:
[0064] Weigh 0.33mmol Co(NO3)2·6H2O and 0.66mmol NH4ReO4, add to 30mL deionized water, stir to dissolve; then add 4mmol C2H4NS, stir for 30min, place in a 50mL reactor, and add a piece of carbon cloth with a size of 2*4, then hydrothermally react in an oven at 200℃ for 20h. After the reaction is completed, rinse the carbon cloth with water and ethanol in turn. After the sample is dried, a carbon cloth-loaded ReS2 / CoS2 Schottky junction composite material is obtained.
[0065] Example 12
[0066] A method for preparing a carbon cloth-supported ReS2 / CoS2 Schottky junction composite material comprises the following steps:
[0067] Weigh 0.33mmol Co(NO3)2·6H2O and 0.66mmol NH4ReO4, add into 30mL deionized water, stir to dissolve; then add 4mmol C2H4NS, stir for 30min, place in a 50mL reactor, add a piece of carbon cloth of size 2*4, then hydrothermally react in an oven at 200℃ for 28h. After the reaction is completed, rinse the carbon cloth with water and ethanol in turn. After the sample is dried, a carbon cloth-loaded ReS2 / CoS2 Schottky junction composite material is obtained.
[0068] Comparative Example 1
[0069] Different from Example 1, only a single metal source NH4ReO4 is added, and other steps remain unchanged to obtain carbon cloth-supported ReS2.
[0070] Comparative Example 2
[0071] On the basis of Example 1, different from Example 1, only a single metal source Co(NO3)2·6H2O is added, and other steps remain unchanged to obtain carbon cloth-supported Co S2.
[0072] Comparative Example 3
[0073] Based on Example 1, the difference from Example 1 is that the molar ratio of cobalt in the added cobalt source and rhenium in the rhenium source is 1:0.5, and the other steps remain unchanged.
[0074] Comparative Example 4
[0075] Based on Example 1, the difference from Example 1 is that the molar ratio of cobalt in the added cobalt source and rhenium in the rhenium source is 1:4, and the other steps remain unchanged.
[0076] Structural characterization
[0077] The carbon cloth-supported ReS2 / CoS2 Schottky junction composite material prepared in Example 1 was physically characterized by TEM, HRTEM, SEM, XRD and UPS. The results are as follows: Figures 1 to 5 shown.
[0078] From SEM( Figure 1 , 2 ) spectrum, it can be seen that the composite material prepared according to the method described in Example 1 is a carbon cloth carrier with a large number of nanosheet arrays grown on the surface. During the reaction process, the interwoven nanosheets and their abundant pores provide a huge electrolyte contact area.
[0079] The material on the surface of the carbon cloth was peeled off by strong ultrasound and characterized by transmission electron microscopy. Figure 3 ) can find abundant lamellar structures, which is consistent with the SEM results; Figure 3 A partial area is enlarged, and the HRTEM ( Figure 4 ) spectrum, it can be seen that the lattice fringes on the nanosheets are 0.607 and 0.275 nm, corresponding to the (001) crystal plane of ReS2 and the (200) crystal plane of CoS2, respectively. Moreover, the two lattice fringes have lattice matching and an interface exists.
[0080] Figure 5 It is the XRD spectrum of the ReS2 / CoS2 Schottky junction composite material supported by carbon cloth. By comparing with the standard spectrum, the diffraction peaks of the material are completely consistent with the standard cards of cubic CoS2 (JCPDS, 65-3322) and triclinic ReS2 (JCPDS, 52-0818), proving the successful formation of CoS2 and ReS2.
[0081] Figure 6 The UPS spectra of ReS2 and CoS2 loaded on carbon cloth prepared in Examples 1 and 2 are shown in Table 1. Through analysis, it can be found that the work function of ReS2 is significantly greater than that of CoS2, which meets the formation conditions of Schottky junction ( Figure 7 a). This means that at the ReS2 / CoS2 interface ( Figure 7 b), electrons spontaneously transfer from CoS2 to ReS2, causing electrons to gather at ReS2 and generating many holes at CoS2, making ReS2 and CoS2 nucleophilic and electrophilic, respectively. The generation of this built-in electric field and the new electronic configuration can provide a fast channel for electron transfer, optimize the adsorption free energy of the electrolytic water splitting reaction and intermediate species, and thus facilitate the catalytic reaction.
[0082] Performance Testing
[0083] 1. Hydrogen evolution performance test
[0084] The hydrogen evolution performance test of the carbon cloth-supported ReS2 / CoS2 Schottky junction composite materials prepared in Example 1, Example 6, and Example 7 and the materials prepared in Comparative Examples 1 to 4 was tested. Test method: A three-electrode test system was used to test using linear sweep voltammetry in a nitrogen-saturated 1.0M KOH solution. The test results are shown in Figure 2. Figure 8 shown.
[0085] Depend on Figure 8 It can be seen that the carbon cloth-loaded ReS2 / CoS2 Schottky junction composite material prepared in Example 1 reaches 10mAcm -2 and 200mA cm -2 When the overpotential is only 108mV and 254mV, respectively, the carbon cloth-supported ReS2 / CoS2 Schottky junction composite material prepared in Example 6 reaches 10mA cm -2 and 200mA cm -2 The overpotentials of 120 mV and 282 mV were required respectively. -2 and 200mA cm -2 When the molar ratio of cobalt to rhenium increases, the catalytic performance shows a "volcano graph" trend. When the molar ratio of cobalt to rhenium is 1:2, the effect is optimal.
[0086] The carbon cloth-loaded ReS2 material prepared in Comparative Example 1 reached 10 mA cm -2 and 200mA cm -2 The overpotentials required were 125 mV and 530 mV respectively. -2 and 200mA cm -2 The overpotentials of 348 mV and 504 mV are required respectively. The hydrogen evolution activity of the materials in Comparative Examples 1 and 2 is significantly lower than that in Example 1, which also shows that the formation of ReS2 / CoS2 Schottky junction plays a significant role in improving the electrocatalytic hydrogen evolution performance.
[0087] The carbon cloth-loaded ReS2 / CoS2 Schottky junction composite prepared in Comparative Example 3 has a high conductivity at 10 mA cm -2 and 200mAcm -2 The overpotentials of 255 mV and 468 mV are required respectively. The hydrogen evolution activity of Comparative Example 3 is reduced because the cobalt content is high and the rhenium content is low, resulting in fewer Schottky junctions and poor regulation effect.
[0088] The carbon cloth-loaded ReS2 / CoS2 Schottky junction composite prepared in Comparative Example 4 was-2 and 200mAcm -2 The overpotentials of 147 mV and 325 mV are required respectively. The hydrogen evolution activity of Comparative Example 4 is reduced because the cobalt content is low and the rhenium content is too high, and the Schottky junctions produced are also less, resulting in poor regulation effect.
[0089] 2. Hydrogen evolution stability test
[0090] The hydrogen evolution stability test of the ReS2 / CoS2 Schottky junction composite material prepared in Example 1 was tested. Test method: A three-electrode test system was used to test using a chronoamperometry method in a nitrogen-saturated 1.0M KOH solution. The test results are shown in Figure 2. Fig. 9 shown.
[0091] Depend on Fig. 9 It can be seen that the current density of the ReS2 / CoS2 Schottky junction composite material prepared in Example 1 has basically not decayed after 56 hours of chronoamperometric testing.
[0092] 3. Oxygen evolution test
[0093] The oxygen evolution performance test of the carbon cloth-supported ReS2 / CoS2 Schottky junction composite material prepared in Example 1 and the materials prepared in Comparative Examples 1-2 was tested. Test method: A three-electrode test system was used to test using linear sweep voltammetry in an oxygen-saturated 1.0M KOH solution. The test results are shown in Figure 2. Fig.10 shown.
[0094] Depend on Fig.10 It can be obtained that the carbon cloth-supported ReS2 / CoS2 Schottky junction composite material prepared in Example 1 has a conductivity of 10 mA cm -2 and 200m Acm -2 When the overpotential is only 246mV and 317mV, respectively, it has excellent catalytic oxygen evolution activity. -2 and 200mA cm -2 The overpotentials of 252 mV and 332 mV were required respectively. -2 and 200mA cm -2 It can be found that similar to the results of hydrogen evolution reaction, as the molar ratio of cobalt to rhenium increases, its catalytic performance shows a "volcano graph" trend, and the effect is optimal when the molar ratio of cobalt to rhenium is 1:2.
[0095] The carbon cloth-loaded ReS2 material prepared in Comparative Example 1 reached 10 mA cm-2 An overpotential of 436 mV is required, and at a limited overpotential, the current density does not reach 200 mA cm -2 The carbon cloth-loaded CoS2 material prepared in Comparative Example 2 reached 10 mA cm -2 and 200mA cm -2 The overpotentials of 345 mV and 444 mV are required respectively. The oxygen evolution activities of Comparative Examples 1 and 2 are significantly lower than those of Example 1, which also shows that the formation of ReS2 / CoS2 Schottky junction plays a significant role in improving the electrocatalytic oxygen evolution performance.
[0096] The carbon cloth-loaded ReS2 / CoS2 Schottky junction composite prepared in Comparative Example 3 has a high conductivity at 10 mA cm -2 and 200mAcm -2 The overpotentials of 273 mV and 368 mV were required for the carbon cloth-supported ReS2 / CoS2 Schottky junction composite prepared in Comparative Example 4. -2 and 200mA cm -2 The overpotentials of 253mV and 382mV were required for the two materials, respectively. The oxygen evolution activity of the two materials decreased, indicating that the appropriate molar ratio of cobalt to rhenium can achieve a better regulation effect on the catalytic behavior of the composite material.
[0097] 4. Oxygen evolution stability test
[0098] The oxygen evolution stability test of the carbon cloth-supported ReS2 / CoS2 Schottky junction composite material prepared in Example 1 was tested. Test method: A three-electrode test system was used to test using a chronoamperometry method in an oxygen-saturated 1.0M KOH solution. The test results are shown in Figure 2. Fig.11 shown.
[0099] Depend on Fig.11 It can be seen that the current density of the carbon cloth-loaded ReS2 / CoS2 Schottky junction composite material prepared in Example 1 has basically not decayed after 56 hours of chronoamperometric testing.
[0100] 5. Full hydrolysis performance test
[0101] The full hydrolysis performance test of the carbon cloth-supported ReS2 / CoS2 Schottky junction composite material prepared in Example 1, and the materials prepared in Comparative Example 1 and Comparative Example 2 was tested. Test method: A dual-electrode test system was used to test the activity using linear sweep voltammetry and the stability using chronoamperometry in an oxygen-saturated 1.0 M KOH solution. The test results are shown in Figure 2. Fig.12 and 13 shown.
[0102] Depend on Fig.12It can be seen that the carbon cloth-loaded ReS2 / CoS2 Schottky junction composite material prepared in Example 1 reaches 10mAcm -2 and 200mA cm -2 When the applied voltage is only 1.64V and 1.86V, respectively, the carbon cloth-supported ReS2 / CoS2 Schottky junction composite material prepared in Example 6 reaches 10mA cm -2 and 200mA cm -2 The applied voltages of 1.65 V and 1.91 V were required respectively. The carbon cloth-supported ReS2 / CoS2 Schottky junction composite material prepared in Example 7 was -2 and 200mA cm -2 When the molar ratio of cobalt to rhenium increases, the electrocatalytic water splitting performance shows a "volcano graph" trend. When the molar ratio of cobalt to rhenium is 1:2, the effect is optimal.
[0103] The carbon cloth-loaded ReS2 material prepared in Comparative Example 1 reached 10 mA cm -2 The carbon cloth-loaded CoS2 material prepared in Comparative Example 2 was - It is worth noting that the ReS2 material prepared in Comparative Example 1 and the CoS2 material prepared in Comparative Example 2 did not reach 200 mA cm under limited applied voltage. -2 It can be found that the bifunctional catalytic activity of Comparative Example 1 and Comparative Example 2 is significantly lower than that of Example 1, which also shows that the formation of ReS2 / CoS2 Schottky junction plays a significant role in improving the electrocatalytic water splitting performance.
[0104] The carbon cloth-loaded ReS2 / CoS2 Schottky junction composite prepared in Comparative Example 3 has a high conductivity at 10 mA cm -2 and 200mAcm -2 The applied voltages of 1.67V and 1.97V were required respectively. The carbon cloth-supported ReS2 / CoS2 Schottky junction composite material prepared in Comparative Example 4 was -2 and 200mA cm -2 The bifunctional catalytic activity of the two materials is lower than that of the composite material prepared in Example 1, indicating that the appropriate molar ratio of cobalt to rhenium can achieve a better regulation effect on the catalytic behavior of the obtained composite material.
[0105] At the same time, after 56h of chronoamperometric testing ( Fig.13), the performance of the composite material is basically not attenuated. This excellent bifunctional catalytic performance is mainly attributed to the electronic structure rearrangement between ReS2 / CoS2 Schottky groups, which optimizes the adsorption free energy of intermediate species in water electrolysis. A series of tests show that the material has broad application prospects as a catalyst for water electrolysis.
Claims
1. A ReS2-based composite material, characterized in that: The invention comprises a carrier and a ReS2 / CoS2 Schottky junction grown on the surface of the carrier, wherein the Schottky junction is a nanosheet array.
2. The ReS2-based composite material according to claim 1, characterized in that The molar ratio of cobalt in the cobalt salt to rhenium in the rhenium source in the ReS2 / CoS2 Schottky junction is 1:(1-3).
3. The ReS2-based composite material according to claim 1, characterized in that The carrier is carbon cloth.
4. A method for preparing a ReS2-based composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: The metal cobalt salt, rhenium source and sulfur source are added to a solvent and mixed, a carrier is added, and then a hydrothermal reaction is carried out. After the reaction is completed, the reaction is rinsed and dried to obtain the ReS2-based composite material.
5. The method for preparing the ReS2-based composite material according to claim 4, characterized in that: The temperature of the hydrothermal reaction is 180-220°C.
6. The method for preparing the ReS2-based composite material according to claim 5, characterized in that: The reaction time is 20 to 28 hours.
7. The method for preparing the ReS2-based composite material according to claim 4, characterized in that: The metal cobalt salt is at least one of cobalt chloride, cobalt nitrate and cobalt sulfate.
8. The method for preparing the ReS2-based composite material according to claim 4, characterized in that: The rhenium source is ammonium perrhenate.
9. The method for preparing the ReS2-based composite material according to claim 4, characterized in that: The sulfur source is thiourea.
10. Use of the ReS2-based composite material described in any one of claims 1 to 3 in the electrolysis of water to produce H2 and O2.